Complete mitochondrial genome sequence and phylogenetic analysis of Myoxocephalus scorpius (Linnaeus, 1758). Issue 1 (2nd January 2019) - Li, Yuan; Song, Puqing; Feng, Ji; Zhang, Nan; Zhang, Ran; Lin, Longshan
Abstract: Myoxocephalus scorpius (Linnaeus, 1758) is the second abundant fish species in coastal Arctic ecosystems with very less genetic information. In this study, the complete mitochondrial genome sequence of M. scorpius was sequenced with 16, 626â€‰bp in length, including the structure of 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and two non-coding regions (origin of light strand replication and control region). All the protein-coding genes use ATG as start codon except COI using GTG. Most of them have TAA or TAG as the stop codon while COII, ND4, and Cyt b use Tâ€". Phylogenetic tree involving all the available Arctic fish was also reconstructed and can provide further genetic analysis for this species.